Growth, Yield, and Stem Quality of Tectona grandis Grown with Different Spacings at Longuza Forest Plantation, Tanzania - Samamba, Enos; Chamshama, Shabani Athumani Omari; Mwambusi, Japhet Noah (Jurnal Manajemen Hutan Tropika, 2024)
Spacing is a silvicultural practice that affects the growth of trees in forest plantations. However, the yield depends on growth, which is determined by spacing. In addition, spacing influences the quantity of the final crop available for harvesting, specifically in forest plantations for sawlog production. Spacing is also used as a management practice to control the quality of trees, as dense stands are expected to have trees with good stem quality. However, little has been done to address the effects of spacing on the growth, yield, and stem quality of Tectona grandis until final harvesting age. Teak plantations in Tanzania are grown at a rotation age of 20 years. Thus, this study aimed to assess the effect of spacing on the growth, yield, and stem quality of 24-year-old T. grandis in a Longuza Forest plantation in Muheza, Tanzania. Data were collected from a spacing trial using a randomized complete block design with three treatments: 2 m × 2 m, 3 × 3 m, and 4 m × 4 m, with three replications. The growth and yield parameters assessed were diameter at breast height (dbh) total tree height, and stem quality. Data were analyzed to obtain the basal area, volume, and mean annual increment. Statistical analysis was performed using analysis of variance (ANOVA), and multiple comparisons among treatment means were performed using Tukey’s honest significant difference test (p-value = 0.05). The results showed that spacing did not significantly affect growth and yield parameters. The stem quality was significantly different in some treatments. The highest dbh and height growth were observed at 4 m× 4 m spacing. The highest values of basal area, volume, and mean annual increment were observed at a 3 m× 3 m spacing. Stem quality differed significantly between the 2 m× 2 m and 4 m× 4 m spacings. Because teak plantations in Tanzania are aimed at sawlog production, it is recommended to continue practising a spacing of 3 m× 3 m, which will ensure a higher mean annual increment with a higher volume at the stand level. In addition, a spacing of 3 m × 3 m ensured a higher percentage of trees with good stem quality.